Opportunities in recreation and leisure careers - Jensen, Clayne R. (McGraw-Hill, 2006)
Are you looking for the latest information to open the door to the career of your dreams? Opportunities in Recreation and Leisure Careers covers a range of jobs in this industry, from those that require high school and trade school to associate, four-year, and graduate degrees. You'll find up-to-date salary statistics, training requirements, as well as the lowdown on life on the job. This comprehensive, no-nonsense guide takes the stress out of launching a career that's both satisfying and financially rewarding.